Caracterización genómica y fenotípica de la especie Brycon henni (Characiformes: Characidae) en cuencas hidrográficas de los ríos Yotoco, Sonso, Guabas y Sabaletas (2021)
Even when there is great diversity and quantity of marine and freshwater species in Colombia, studies regarding the phylogenetic relationships of fish species in the country are still insufficient, despite the need for rigorous characterization of the local fish fauna. The objective of the present investigation was to characterize the freshwater species Brycon henni in hydrographic basins located in four municipalities of the department of Valle del Cauca-Colombia, through the use of barcode and geometric morphometry. A highly conserved nuclear gene that could be easily amplified and sequenced (RAG1) was used, as well as the 16S rRNA and COI mitochondrial regions. The results showed an identification of four species Brycon sp., for the individuals collected in Sabaletas (Buenaventura), Brycon henni for the individuals from Guabas, Sonso and Yotoco, Bryconamericus caucanus for two individuals collected in Guabas and finally Creagrutus sp. for five individuals collected in Yotoco. For geometric morphometry, images were used and a total of nine marks were recorded in each individual. The results indicated a complete separation of the Brycon sp. and Brycon henni through body structure. Likewise, a marked separation is observed with the individuals of the species Creagrutus sp. and Bryconamericus caucanus.